The Effect of Sapodilla Leaves (Achras Zapota) Infusum towards Mice (Mus Muculus) Diarrheal Activity Induced by Oleum Ricini - Glabela Christiana Pandango; Ramadhani R. B; Irfiansyah Irwadi (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Diarrhea is a significant health problem, especially in countries with low income. In many cases, diarrhea even can cause death. Treatment for diarrhea has been done both pharmacologically (including the usage of herbal remedies) and non-pharmacologically. Decoction of the sapodilla’s leaves is often used to treat diarrhea, but no studies directly demonstrates the effects of sapodilla’s leaves’ decoction towards living creatures. The purpose of this study was to determine the effect of sapodilla leaves’ (Achras zapota) infusum towards diarrheal activity of mice (Mus musculus) which can be seen through the onset and frequency of diarrhea, and the consistency and quantity / weight of feces.Methods: 30 mice were divided into five groups. Negative controls (group I) were administered with oleum Ricini, positive controls (group II) were administered with oleum Ricini and Loperamide HCl after half-an hour, and group III, IV, and V, were administered with oleum Ricini and sapodilla leaves’ (Achras zapota) infusum ( with the concentration of 5 g %, 10 g %, and 20 g %) after half-an hour. Then, those mice were observed for 3 hours for their diarrheal activity (diarrheal onset, frequency, fecal consistency, and fecal weights).Results: Analysis by Kruskal-Wallis method showed significant differences of diarrheal activities among the five groups (p = 0.023). Whilst, analysis by Mann-Whitney method showed significant differences between group I and II (p = 0.04), group I and III (p = 0.012), and group I and IV (p = 0.006).Conclusions: Based on the result showed sapodilla leaves’ (Achras zapota) infusum could reduce diarrheal activity of mice (Mus musculus).